Complications of Enterocutaneous Fistulas and Their Management - Williams, Lara J. (Thieme Medical Publishers, 2010)
Complications related to enterocutaneous fistulas are common and include sepsis, malnutrition, and fluid or electrolyte abnormalities. Intestinal failure is one of the most feared complications of enterocutaneous fistula management and results in significant patient morbidity and mortality. The authors review emerging trends in the medical and surgical management of patients with intestinal failure.